2018
DOI: 10.1186/s13756-018-0387-0
|View full text |Cite
|
Sign up to set email alerts
|

Intra-hospital differences in antibiotic use correlate with antimicrobial resistance rate in Escherichia coli and Klebsiella pneumoniae: a retrospective observational study

Abstract: BackgroundMonitoring antimicrobial use and resistance in hospitals are important tools of antimicrobial stewardship programs. We aimed to determine the association between the use of frequently prescribed antibiotics and the corresponding resistance rates in Escherichia coli and Klebsiella pneumoniae among the clinical departments of a tertiary care hospital.MethodsWe performed a retrospective observational study to analyse the use of nine frequently prescribed antibiotics and the corresponding antimicrobial r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 21 publications
4
13
2
1
Order By: Relevance
“…In accordance with previous studies, our results found that the FQR E. coli was significantly associated with FQs consumption [9][10][11][12][13][14][15][16][17][18] . The most important resistance mechanism of E. coli to quinolones is mutation of target gene DNA gyrase and topoisomerase IV.…”
Section: Correlation Between Antibiotics Consumption Intensity and Fqrsupporting
confidence: 93%
“…In accordance with previous studies, our results found that the FQR E. coli was significantly associated with FQs consumption [9][10][11][12][13][14][15][16][17][18] . The most important resistance mechanism of E. coli to quinolones is mutation of target gene DNA gyrase and topoisomerase IV.…”
Section: Correlation Between Antibiotics Consumption Intensity and Fqrsupporting
confidence: 93%
“…However, the correlation of ciprofloxacin-resistant A. baumannii and the antibiotics consumption was not found. Consistant with previous studies, our results found that the FQR E. coli was significantly associated with FQs consumption [10][11][12][13][14][15][16][17][18][19]. The most important resistance mechanism of E. coli to quinolones is mutation of target gene DNA gyrase and topoisomerase IV.…”
Section: Discussionsupporting
confidence: 69%
“…The low influence of connectivity on the incidence of resistant E. cloacae complex variants can be explained by their local selection. While resistance in E. coli and K. pneumoniae typically requires gene acquisition 34,35 , E. cloacae complex can resist cephalosporins and carbapenems through increased AmpC betalactamase and decreased porin expression [36][37][38] . Such resistance emerges through adaptation and de novo mutations that are rapidly selected from the local reservoir of susceptible progenitors 39,40 .…”
Section: Discussionmentioning
confidence: 99%
“…The rationale behind hospital-based antibiotic stewardship is based on the assumption that AMR evolves in hospitals. Yet, there is surprisingly limited evidence to support this assumption [36][37][38] . Ecological studies have repeatedly identified associations between the use of antibiotics and AMR prevalence, but such associations do not necessarily reflect AMR selection 19 .…”
Section: Discussionmentioning
confidence: 99%